Contribution of hand and leg movements to the throwing performance of water polo players - Komori, Y.; Kitada, K.; Segwa, E.; Shimura, Y.; Kono, I. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Throwing is one of the most important skills in water polo. However, the throwing movement in water differs from that on dry land since no ground support is available in the water. Throwing movements in the water require the use of highly complicated and very important underwater techniques, such as sculling (hand movements) and eggbeater kicking (lower leg movements). Therefore, the present study aimed to examine the contribution of the body parts to throwing performance, particularly the effect of hand movements and lower leg movements on throwing velocity in the water. Methods: A total of 19 male high school water polo players participated in this study. Each player threw the ball three times for each pattern using three different penalty throw patterns while shooting at the goal. The throwing patterns were as follows: normal; one arm immobilized (AI); and both lower legs immobilized (LI). The following indicators of throwing performance were used: initial throwing velocity detected using speed gun Doppler ultrasonography, and head height at the moment of ball release using a high-speed video camera. Results: The mean initial throwing velocities of the normal, AI, and LI patterns were 60.0 ± 5.7 km/h, 56.6 ± 4.5 km/h, and 49.9 ± 4.6 km/h, respectively. AI and LI throwing velocities were lower than that of the normal pattern. The LI pattern showed a 16.8% depreciation compared with the normal pattern. Furthermore, head heights at ball release in the AI and LI patterns were lower than that in the normal pattern. Discussion: On dry land, the throwing velocity of the LI pattern showed a depreciation of 16.0 % compared with that of the normal pattern (Toyoshima, 1973). The present study showed a similar rate of decrease in the LI pattern throwing velocity compared with the normal pattern throwing velocity, suggesting a similar contribution of the lower legs to throwing velocity in water compared to that on dry land. A correlation between throwing velocity and water jump height was noted in water polo players (Ross, 1999). The present study showed that the head height at ball release in the LI pattern was lower than that in the Normal throwing pattern.Therefore, the use of an underwater technique involving the legs that raises the body high above the surface of the water appears to be required to maintain throwing velocity. In conclusion, the results of this study suggest that lower leg movements are an important factor of throwing performance in the water.